STUDENTS' CRITICAL THINKING ABILITY ON GLOBAL WARMING MATERIAL AT PARIAMAN HIGH SCHOOL - Atika, Atika (PILLAR OF PHYSICS EDUCATION, 2024)
21st century learning in the era of globalization requires students to have abilities that can help them face the demands of contemporary developments. Of the various abilities demanded in the 21st century, students must possess critical thinking skills in order to navigate life's challenges and competition. Practicing this ability is certainly carried out by all subjects including physics. One of the materials in physics subjects is global warming. Different initiatives have been undertaken to cultivate a generation equipped with abilities relevant to the 21st century, particularly emphasizing critical thinking to address everyday challenges, primarily through the utilization of an independent curriculum. However, in reality, learning physics is often considered a difficult lesson, students tend to learn by memorizing topics rather than investigating, analyzing and solving real world problems, so critical thinking abilities are less developed. This study aims to outline students' critical thinking abilities in relation to global warming content. Descriptive research is the method of research that was utilized. The research was conducted at three high schools in Pariaman. A total of 79 students were given a critical thinking ability test with the instrument used in the form of a 10-question essay. Overall, the research results show that the average critical thinking ability of students is still very low with a score of 39.16. Based on the results of the analysis, the highest score was obtained for the aspect of providing simple clarification. This is followed by aspects of strategy and tactics, aspects of building basic skills, concluding and making further clarifications in the very low category.